Effect of embedded optical fibres on the mechanical properties of cochlear electrode arrays. Issue 2 (February 2016) - Carland, Emma M.; Stoddart, Paul R.; Cadusch, Peter J.; Fallon, James B.; Wade, Scott A.
Highlights: Studied incorporation of optical fibres into cochlear electrode arrays. Measured mechanical properties of cochlear electrode arrays (deflection force). Measured mechanical properties of optical fibre (deflection and buckling forces). 50 µm optical fibre embedded in an electrode array should not affect stiffness. Abstract: Incorporating optical fibres in cochlear electrode arrays has been proposed to provide sensors to help minimise insertion trauma and also for the delivery of light in optical nerve stimulation applications. However, embedding an optical fibre into an electrode array may change its stiffness properties, which can affect the level of trauma during insertion. This report uses measurements of buckling and deflection force to compare the stiffness properties of a range of cochlear electrode arrays (Nucleus straight array, rat array, cat array and guinea pig array) with custom arrays containing an embedded optical fibre. The cladding diameters of the optical fibres tested were 125 µm, 80 µm and 50 µm. The results show that the stiffness of the optical-fibre-embedded arrays is related to the diameter of the optical fibre. Comparison with wired arrays suggests optical fibres with a diameter of 50 µm could be embedded into an electrode array without significantly changing the stiffness properties of the array.